The Saudi Digital Library participates in the third national symposium on the practices and challenges of acquiring digital content in “KAUST” | المكتبة الرقمية السعودية تشارك في الندوة الوطنية الثالثة عن ممارسات وتحديات استحواذ المحتوى الرقمي في” كاوست ” - Al-Mutairi | المطيري, Salman bin Salem | سلمان بن سالم; AlRakhis | الرخيص, Abdullah | عبد الله; Mohammed | محمد, Mervat Reda Ahmed Hassanein | مرفت رضا أحمد حسنين (Saudi Digital Library | المكتبة الرقمية السعودية, 2023)
The Saudi Digital Library delegation, headed by the General Supervisor, attended the third national symposium organized by the King Abdullah University of Science and Technology (KAUST) Library, at the university's campus in Thuwal, on the practices and challenges of acquiring digital content in the library, led by the Director of the KAUST Library and the official spokesperson for this symposium. The symposium is one of the initiatives of the awareness program led by Dr. Nada Morsi, senior librarian and outreach specialist, with the participation of the library acquisition team. The symposium brought together a number of librarians from 15 universities and institutions from across the Kingdom and more than 25 participants to learn about the university library’s experiences in the field of acquisition and digitization. | حضر وفد المكتبة الرقمية السعودية برئاسة المشرف العام الندوة الوطنية الثالثة التي تنظمها مكتبة جامعة الملك عبدالله للعلوم والتقنية “كاوست”، في مقر الجامعة في ثول، عن ممارسات وتحديات استحواذ المحتوى الرقمي في المكتبة بقيادة مدير مكتبة كاوست، والمتحدث الرسمي لهذه الندوة. وتعد الندوة أحد مبادرات برنامج التوعية بقيادة الدكتورة ندى مرسي كبير أمناء المكتبة وأخصائية التوعية وبمشاركة فريق الاستحواذ من المكتبة، وقد جمعت الندوة عدد من أمناء المكتبات من 15 جامعة ومؤسسة من انحاء المملكة واكثر من 25 مشارك للتعرف على تجارب مكتبة الجامعة في مجال الاستحواذ والرقمنة.